Does the GNB3 C825T polymorphism influence swimming performance in competitive swimmers? - Grenda, A.; Sawczuk, M.; Kaczmarczyk, M.; Maciejewska, A.; Umiastowska, D.; Lubkowska, W.; Zmijewsk, P.; Cieszczyk, P. (Journal of Human Kinetics, 2015)
Single nucleotide polymorphism C825T located within the GNB3 gene has been proposed in the literature as the performance enhancing polymorphism in highly trained athletes. Therefore, the aim of the present study was to verify the hypothesis assuming an association between the C825T polymorphic site and performance of competitive swimmers. The frequencies of C/T alleles and distribution of CC, CT and TT genotypes of the C825T GNB3 polymorphism were compared between athletes and nonathletic controls as well as between sprint and endurance swimmers. Genomic DNA was extracted from 197 competitive swimmers (50 long distance swimmers (LDS) and 147 short distance swimmers (SDS)) and 379 sedentary volunteers. The allele frequencies and genotype distribution of the C825T polymorphic site were not significantly different when LDS and SDS were compared to sedentary controls. Gender-specific analysis did not reveal any significant differences in allele and genotype distribution, neither between female controls and female swimmers nor between male controls and male swimmers. No significant differences in allele frequencies and genotype distribution were observed when LDS and SDS as well as groups of swimmers stratified by gender were compared. The results of this study do not support the hypothesis that the C825T polymorphism of the GNB3 gene is associated with swimming performance in competitive swimmers.